PENDIDIKAN GEOSISTA SEBAGAI UPAYA MEMINIMALKAN PENGGUNAAN GADGET PADA ANAK: SEMINAR-WORKSHOP UNTUK GURU DAN ORANG TUA - Khusnul Khotimah; Agus Saputra; Baiq Niswatul Khair; Susi Rahayu (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2021)
Currently, the use of gadgets has been rampant in all levels of society, including among children. Uncontrolled use of gadgets has more negative impacts, both from social, health, academic and psychosocial aspects. In this regard, the role of parents and teachers is needed to anticipate or reduce the negative impact of using gadgets. However, an understanding of the dangers of gadgets to children and how to prevent or overcome them is not necessarily understood comprehensively by parents and teachers. Seeing these conditions, an innovative activity was carried out which aims to 1) provide an understanding of the dangers of exposure to gadgets and social media in children and 2) socialize and demonstrate the concept of geoscience education and geo-tourism based on geopark as an alternative to reduce gadget exposure to children, as well as enrich practical experiences using the concept of geoscience and geotourism (geosista). This activity is designed for teachers and parents with the hope of being a source of inspiration and also as a guide to be practiced when with children both at school and at home. The concept of GEOSISTA (geoscience and geo-tourism based on Geopark) is considered important for the people of the island of Lombok by considering the potential of a landscape that can provide benefits in both economic, social and cultural aspects. The activities, which are packaged in the form of seminars and workshops, are felt to have an impact on increasing participants' understanding and skills in applying the Geosista concept as an effort to reduce gadget dependence on children. In addition, building a generation that has a strong character in preserving the environment through science can be expected to be a joint mission, both for teachers and parents